In Vivo Evaluation of Complex Biogenic Silver Nanoparticle and Enoxaparin in Wound Healing. (29th March 2015) - Marcato, P. D.; De Paula, L. B.; Melo, P. S.; Ferreira, I. R.; Almeida, A. B. A.; Torsoni, A. S.; Alves, O. L.
Abstract : The burns treatment is difficult, uncomfortable for the patient, and expensive for health system. Due to antimicrobial properties of silver nanoparticles (AgNP), these particles can avoid bacterial infection in wound and accelerate the wound healing. Furthermore, the complexation of AgNP with enoxaparin (low molecular weight heparin) may improve the healing process of lesions due to anti-inflammatory and angiogenic activity of enoxaparin (Enox). The aim of this study was evaluated the activity and toxicity of biogenic AgNP and AgNP complexed with Enox in in vivo burn wound model. AgNP was produced by biosynthesis method using Fusarium oxysporum . AgNP (20–40 nm) exhibited high stability due to protein capping around the particles that was confirmed by TEM, fluorescence spectroscopy, and FTIR. The wound contraction in in vivo model, after 28 days of treatment, was 55, 89, 91, and 95% for control, Enox, AgNP, and AgNP-Enox groups, respectively. No clear toxic effects in the biochemistry and hematological parameters were verified in all treated groups. However, in the AgNP-Enox group, a statistically significant increase in the urea levels was observed indicating increased proteolysis due to inflammation process. The results demonstrated that the complex AgNP-Enox is interesting for wound healing decreasing the time of lesions healing.